TatBC, TatB, and TatC form structurally autonomous units within the twin arginine protein transport system of Escherichia coli. - Orriss, G; Tarry, M; Ize, B; Sargent, F; Lea, S; Palmer, T; Berks, B (2007)
The Tat (twin arginine translocation) system transports folded proteins across bacterial and thylakoid membranes. The integral membrane proteins TatA, TatB, and TatC are the essential components of the Tat pathway in Escherichia coli. We demonstrate that formation of a stable complex between TatB and TatC does not require TatA or other Tat components. We show that the TatB and TatC proteins are each able to a form stable, defined, homomultimeric complexes. These we suggest correspond to structural subcomplexes within the parental TatBC complex. We infer that TatC forms a core to the TatBC complex on to which TatB assembles.